Modern enterprise architecture : using DevSecOps and cloud-native in large enterprises - Mulder, Jeroen (Apress, 2023)
Enterprise Architecture (EA) frameworks such as TOGAF and Zachman are still valid, but enterprise architects also need to adapt to the new reality of agile, DevOps, and overall disruption through digital transformation. This book will help do just that. The Change to Modern Enterprise Architecture will teach you how to use known frameworks in the new world of digital transformation. Over the course of the book, you'll learn how modern EA is helping drive strategic business decisions, create continuous and agile (“floating”) architecture for scalability, and how to address quality and speed in architecture using and integrating DevSecOps frameworks in EA. This book is divided into three parts: the first explains what modern enterprise architecture is and why it’s important to any business. It covers the different EA frameworks and explains what they are. In the second part, you will learn how to integrate modern development frameworks into EA, and why this knowledge will enable you to deftly respond to various business challenges. The final section of the book is all about scaling the enterprise using modern enterprise architecture. You will also see how the role of the enterprise architect is changing and how to remain in control of your architecture. Upon completing this book, you'll understand why the enterprise architect is no longer just a role overseeing the architecture strategy of a business, but has become more of a leader in driving engineering excellence.